Colour and motion affect a dune wasp’s ability to detect its cryptic spider predators - Rodríguez-Morales, Dulce (Sci Rep, 2021)
Ambush predators depend on cryptic body colouration, stillness and a suitable hunting location to optimise the probability of prey capture. Detection of cryptic predators, such as crab spiders, by flower seeking wasps may also be hindered by wind induced movement of the flowers themselves. In a beach dune habitat, Microbembex nigrifrons wasps approaching flowerheads of the Palafoxia lindenii plant need to evaluate the flowers to avoid spider attack. Wasps may detect spiders through colour and movement cues. We tracked the flight trajectories of dune wasps as they approached occupied and unoccupied flowers under two movement conditions; when the flowers were still or moving. We simulated the appearance of the spider and the flower using psychophysical visual modelling techniques and related it to the decisions made by the wasp to land or avoid the flower. Wasps could discriminate spiders only at a very close range, and this was reflected in the shape of their trajectories. Wasps were more prone to making errors in threat assessment when the flowers are moving. Our results suggest that dune wasp predation risk is augmented by abiotic conditions such as wind and compromises their early detection capabilities.